Rancang Bangun Sistem Informasi Inventory Untuk Mengontrol Persediaan Pada PT.Gotrans Logistics International - abiyyu, riski; Bagja, Bagja Rahmat Mubarak (Institut Riset dan Publikasi Indonesia, 2021)
Inventory system is a system for managing inventory in the warehouse. Inventory system is now widely used by companies developing in general. Especially in terms of data management stuff. PT.Gotrans Logistics company engaged in delivery in the province of Riau where the activity of good and effective performance must be maintained and improved. Like managing, search, entry and exit flow of goodsand report the data items when it’s needed. Based on these problems, the company has a desire to better utilize information technology through the development of an inventory system, because the system of data management activities good in storage at this time have not felt up by the company. This inventory system using metode Waterfall. UML (Unified Modeling Language) as a data flow model. PHP programming language, and database MySQL. The system is built with the concept of user friendly, so the system is made with an easy to understand interface and made attractive.